Bosnia and Herzegovina : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses key findings of the Financial System Stability Assessment on Bosnia and Herzegovina (BiH). The financial system in BiH is still dealing with the aftershocks of the global financial crisis as well as deep-seated vulnerabilities. A high system-wide nonperforming loan ratio reflects the impact of the crisis, low growth since then, and a history of lax lending policies. Bank governance problems, weak supervision powers, and related-party loans are obstacles to addressing asset quality problems and re-establishing bank profitability. Banking and insurance oversight have improved since the 2006 Financial Sector Assessment Program, but supervisors' corrective and enforcement powers are weak and identifying ultimate beneficial owners and related-party lending is problematic.